2021
DOI: 10.1111/jdv.17499
|View full text |Cite
|
Sign up to set email alerts
|

Development of eruptive pseudoangiomatosis following COVID‐19 immunization – Apropos of 5 cases

Abstract: progressive improvement of pruritus was noted. The eruption regressed spontaneously after 3 weeks.Among the cutaneous manifestations of COVID-19 infection, maculopapular rashes account for almost 50% of cases. 3 Rarely, these may resemble or are identical to PR. Ehsanixi et al. recently reported an otherwise healthy young man with a typical PR eruption concurrent with COVID-19 pneumonia. 4 Isolated reports of PR developing in asymptomatic patients have also been described. 5 Drug-induced PR-like eruptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Vascular lesions including eruptive cherry angiomas have been reported secondary to COVID-19, which could be mediated by angiotensin-converting enzyme 2 (ACE2) receptors; subsequent endothelial damage has also been reported [5,6]. Mohta et al have reported 12 cases of eruptive pseudoangiomatosis, a similar vascular lesion that commonly occurs in the pediatric age group and is associated with ChAdOx1 nCoV-19 coronavirus vaccine (recombinant) in India [7]. The possible vascular injury [8,9] or immune dysregulation [10] caused by the COVID-19 vaccination could play a role in the development of these eruptive vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular lesions including eruptive cherry angiomas have been reported secondary to COVID-19, which could be mediated by angiotensin-converting enzyme 2 (ACE2) receptors; subsequent endothelial damage has also been reported [5,6]. Mohta et al have reported 12 cases of eruptive pseudoangiomatosis, a similar vascular lesion that commonly occurs in the pediatric age group and is associated with ChAdOx1 nCoV-19 coronavirus vaccine (recombinant) in India [7]. The possible vascular injury [8,9] or immune dysregulation [10] caused by the COVID-19 vaccination could play a role in the development of these eruptive vascular lesions.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Till date, only 6 cases of EP secondary to COVID‐19 vaccine have been reported in literature. 4 , 5 The proposed hypothesis is upregulation of cellular and humoral immunity against the spike protein in the viral vaccine stimulating a paraviral response. 5 In our experience, the estimated incidence of EP following COVID‐19 vaccination is as low as 0.03%.…”
Section: Figurementioning
confidence: 99%
“…4,5 The proposed hypothesis is upregulation of cellular and humoral immunity against the spike protein in the viral vaccine stimulating a paraviral response. 5 In our experience, the estimated incidence of EP following COVID-19 vaccination is as low as 0.03%. According to our results, EP is predominantly a disease of younger age groups.…”
Section: Clinical Histopathological and Dermatoscopic Characterizatio...mentioning
confidence: 99%
“…Anti-SARS-CoV-2 vaccine-related cutaneous vascular eruptions have also been recorded, with six cases of EP (Covishield, 5; ModernaCambridge, MA, USA, 1) 7,8 and one of eruptive cherry angiomas 9 described to this date (Pfizer; Table 1).…”
mentioning
confidence: 99%